Features of mental health service provision during the COVID-19 pandemic in specialists who work with suicide prevention in rural areas - Čepulienė, Austėja Agnietė; Dadašev, Said; Grigienė, Dovilė; Marcinkevičiūtė, Miglė; Uržaitė, Greta; Rimkevičienė, Jurgita; Umbrasaitė, Ignė (Psichologija, 2021)
The COVID-19 pandemic can influence the situation of suicide rates and mental health in rural regions even more than in major cities. The aim of the current study was to explore the functioning of mental health service provision during the COVID-19 pandemic through interviews with mental health professionals and other specialists who work with suicide prevention in rural areas. Thirty specialists were interviewed using a semi-structured interview format. The following codes were identified during the thematic analysis: providing help during the pandemic (mental health professionals and institutions adapted to the conditions of the pandemic, remote counselling makes providing help more difficult, the help is less reachable); help-seeking during the pandemic (people seek less help because of the pandemic, seeking remote help is easier, the frequency of help seeking didn’t change); the effects and governing of the pandemic situation (the pandemic can have negative effects on mental health; after the pandemic mental health might get worse; the governing of the pandemic situation in Lithuania could be more fluent). The current study reveals positive aspects of mental health professionals’ adaptivity during the pandemic, as well as severe problems which are related to the access to the mental health services during the COVID-19 pandemic.